Aspek Sosial Selective Exposure dalam Pemberitaan Gempa Bumi Sumedang di Instagram @Inimahsumedang - Rahmani, Aykaputri Amalia; Mulyani, Henny Sri; Kusmayadi, Ika Merdekawati (Universitas Prof. Dr. Moestopo (Beragama), 2025)
National media typically adopt disaster journalism when reporting on disasters. However, local media increasingly highlight these issues due to their high news value in terms of proximity. Advances in technology and societal changes have made people more selective about the information they consume, particularly on social media, including disaster-related news that impacts many lives. This study aims to describe the selective exposure behavior of high school students in Sumedang Regency toward news about the Sumedang earthquake on Instagram @Inimahsumedang, focusing on social aspects such as emotional support, informational support, and social norms. A quantitative descriptive approach was employed, utilizing descriptive statistical analysis, including median, mode, minimum, and maximum values. Additionally, the study examines differences in news selection behavior between male and female high school students in Sumedang Regency using an independent T-test (two-tailed). The findings reveal that social aspects influence individuals' selective exposure to news about the Sumedang earthquake on Instagram @Inimahsumedang. However, the T-test suggesting no significant differences in news selection behavior between male and female students regarding the social aspects of the issue.